Endothelial cell dysfunction in globoid cell leukodystrophy. Issue 11 (1st April 2016) - Belleri, Mirella; Presta, Marco
Abstract : Angiogenesis plays a pivotal role in the physiology and pathology of the brain. Microvascular alterations have been observed in various neurodegenerative disorders, including genetic leukodystrophies. Globoid cell leukodystrophy (GLD) is a lysosomal storage disease caused by β‐galactosylceramidase (GALC) deficiency and characterized by the accumulation of the neurotoxic metabolite psychosine in the central nervous system and peripheral tissues. Structural and functional alterations occur in the microvascular endothelium of the brain of GLD patients and twitcher mice, a murine model of the disease. In addition, increased vessel permeability and a reduced capacity to respond to proangiogenic stimuli characterize the endothelium of twitcher animals. On the one hand, these alterations may depend, at least in part, on the local and systemic angiostatic activity exerted by psychosine on endothelial cells. On the other hand, studies performed in vivo on zebrafish embryos and in vitro on human endothelial cells suggest that GALC downregulation may also lead to psychosine‐independent neuronal and vascular defects. Together, experimental observations indicate that endothelial cell dysfunctions may represent a novel pathogenic mechanism in human leukodystrophies, including GLD. A better understanding of the molecular mechanisms responsible for these microvascular alterations may provide new insights for the therapy of GLD. © 2016 Wiley Periodicals, Inc. Abstract : A tight trophic cross‐talk exits between endothelial and glial/neuronal compartments in the CNS. β‐Galactosylceramidase deficiency in globoid cell leukodystrophy causes accumulation of the toxic metabolite psychosine in the brain, leading to neurotoxic effects, angiosuppression, and endothelial cell damage. Psychosine‐independent alterations may also contribute to neuronal and vascular defects in the brain and peripheral tissues, with endothelial dysfunction representing a possible novel pathogenic mechanism in human leukodystrophies.